2017
DOI: 10.28991/cej-2017-00000085
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art: Mechanical Properties of Ultra-High Performance Concrete

Abstract: During the past decades, there has been an extensive attention in using Ultra-High Performance Concrete (UHPC) in the buildings and infrastructures construction. Due to that, defining comprehensive mechanical properties of UHPC required to design structural members is worthwhile. The main difference of UHPC with the conventional concrete is the very high strength of UHPC, resulting designing elements with less weight and smaller sizes.  However, there have been no globally accepted UHPC properties to be implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The design elastic modulus (Ecd) is given by: Ecd = Ecm 1.3 (25) Ecm is the mean value of elastic modulus. The compression strain at maximum loading (Ԑc2) is given by: Ԑc2 = 𝑓𝑐𝑑 𝐸𝑐𝑑 (26) Ԑc2 is used when UHPC is without fibers or little fiber content, i.e., when the brittle behavior dominates. However, when fiber content is relatively high, the softening behavior occurs, and it must be considered in the design to represent the post-peak strain beyond Ԑc2.…”
Section: Stress-strain Curve In Compression For the Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The design elastic modulus (Ecd) is given by: Ecd = Ecm 1.3 (25) Ecm is the mean value of elastic modulus. The compression strain at maximum loading (Ԑc2) is given by: Ԑc2 = 𝑓𝑐𝑑 𝐸𝑐𝑑 (26) Ԑc2 is used when UHPC is without fibers or little fiber content, i.e., when the brittle behavior dominates. However, when fiber content is relatively high, the softening behavior occurs, and it must be considered in the design to represent the post-peak strain beyond Ԑc2.…”
Section: Stress-strain Curve In Compression For the Designmentioning
confidence: 99%
“…The very high compressive strength of UHPC leads to the design of structural members with smaller sizes and lightweight than the NSC or HSC under the same loading [26].…”
Section: Mechanisms Of Shear Failure In Rc Beamsmentioning
confidence: 99%
“…This is the main factor in the evaluation of the bearing capacity of the supports. Its correct estimate is subject of continuous research [24,25,26,27]. ACI 318 sets out two different equations for determining flexural rigidity.…”
Section: Wherementioning
confidence: 99%
“…Acknowledging the need to reduce these interventions, durable material, such as ultra-high performance concrete (UHPC), has recently been used for strengthening and repair of existing structures. Past research has shown improvement in the structural performance of existing structures when UHPC is used as a retrofitting material (1)(2)(3)(4). The high density, low permeability, and chloride resistance of UHPC makes it an ideal protective layer against corrosion, weathering, and chemical attack (5).…”
mentioning
confidence: 99%